Contemporary Issues in Childhood Diarrhoea and Malnutrition - Edited by Zulfiqar Ahmed Bhutta (Karachi, Pakistan Oxford University Press, 2000)
This is the most recent and up-to-date compilation of articles exploring the scientific and public health aspects of childhood diarrhoea and malnutrition. Written jointly by authors from developed and developing countries, it is essential reading for health workers and postgraduate students.
Include Figures, Illustration, Tables and Index.
It is a Conference publication.
Keywords: Malnutrition in children -- Diarrhea in children -- Child Nutrition Disorders